2017
DOI: 10.1080/00074918.2017.1298719
|View full text |Cite
|
Sign up to set email alerts
|

Gravity Models of Interregional Migration in Indonesia

Abstract: This article explores the determinants of interregional migration in Indonesia. Employing basic and modified (extended) gravity models, and using data from the 2000 and 2010 Population Censuses and the 2005 Intercensal Population Survey, we test Long's (1985) hypothesis that in the early stages of population redistribution, economic development is positively related to a concentration of the population. Using per-capita GDP as a proxy for income and as an indicator of economic development, we find that migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 43 publications
(87 reference statements)
7
35
0
Order By: Relevance
“…In the case of Indonesia, Jakarta is known for its relatively low air quality, congestion, and high density. A study by Wajdi et al (2015) showed that Jakarta had larger outflows to than corresponding inflows from Bodetabek (a metro area surrounding Jakarta), indicating a preference for low-density locations over Jakarta.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of Indonesia, Jakarta is known for its relatively low air quality, congestion, and high density. A study by Wajdi et al (2015) showed that Jakarta had larger outflows to than corresponding inflows from Bodetabek (a metro area surrounding Jakarta), indicating a preference for low-density locations over Jakarta.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In terms of the migration-development relationship, some studies (see for example Wajdi et al 2015;World Bank 2012) have shown that migration is directed towards more developed regions; that is, metropolitan areas in Java. The World Bank (2012) utilised GDP divided by the size of the urban land area to measure the economic density of a region and showed that the metropolitan areas in Java have a high economic density as a further evidence of the gap in economic development.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors may prevent workers from migrating on a large scale. The presence of a more attractive labour force can attract more investment, which may in turn reinforce and prolong development disparities between regions (e.g., Kunz, 2012;Wajdi, Adioetomo, & Mulder, 2017). Commuting behaviour (interregional spatial mobility) seems to provide an intermediate solution, especially if developed regions with low unemployment rates are located next to regions with high unemployment rates (Clemente, Larramona, & Olmos, 2016;Kosfeld, 2007;Rijnks, Koster, & McCann, 2016).…”
Section: Introductionmentioning
confidence: 99%